2005
DOI: 10.1007/s00535-004-1532-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of video capsule endoscopy for evaluating obscure gastrointestinal bleeding: usefulness of early use

Abstract: Our data suggest that the optimal timing to perform VCE is within a few days after the occurrence of bleeding, possibly within 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
3
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 15 publications
(9 reference statements)
5
80
3
11
Order By: Relevance
“…This is also reflected by the matched odds ratios comparing VCE and MPCTE to DBE where there were no increased odds of finding a bleeding site at DBE compared to VCE and increased odds at DBE compared to MPCTE. In our data, none of the tests had a significantly higher yield in patients with overt bleeding compared to occult bleeding, which is unlike prior studies [23][24][25] In conclusion, our data suggest that DBE is a generally safe and well tolerated procedure for the diagnosis and treatment of OGIB, with a diagnostic yield that may be increased after obtaining a preceding VCE or MPCTE. However, inpatients with active ongoing bleeding may benefit from proceeding directly to antegrade DBE, which has the benefits of improved diagnostic yield in these patients, ability to intervene therapeutically, and avoidance of an additional diagnostic test.…”
Section: Discussioncontrasting
confidence: 97%
“…This is also reflected by the matched odds ratios comparing VCE and MPCTE to DBE where there were no increased odds of finding a bleeding site at DBE compared to VCE and increased odds at DBE compared to MPCTE. In our data, none of the tests had a significantly higher yield in patients with overt bleeding compared to occult bleeding, which is unlike prior studies [23][24][25] In conclusion, our data suggest that DBE is a generally safe and well tolerated procedure for the diagnosis and treatment of OGIB, with a diagnostic yield that may be increased after obtaining a preceding VCE or MPCTE. However, inpatients with active ongoing bleeding may benefit from proceeding directly to antegrade DBE, which has the benefits of improved diagnostic yield in these patients, ability to intervene therapeutically, and avoidance of an additional diagnostic test.…”
Section: Discussioncontrasting
confidence: 97%
“…The authors found higher diagnostic value in patients who underwent earlier CE. [9] It has been proposed in international consensus meetings that earliest CE performance should be within the first 2 weeks of symptom observation.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines developed by Gerson et al are presented here as an example. [8][9][10][11][12][13][14][15][16][17][18] Our algorithm is shown in Figure 5.…”
Section: Yes Nomentioning
confidence: 99%
“…(Pennazio M et al, 2004;Appleyard MN et al, 2006;Gupta R et al, 2006;Ersoy O et al, 2006;Lewis BS et al, 2002;Appleyard M et al, 2001;Rastogi A et al, 2004) The indications for CE investigations are somewhat limited, and insufficient evidence currently prevents its use on a larger scale ( 2005 and 2006) recommend that the procedure should be performed within the first two weeks following patient admission , as it has been proven that early use dramatically increases the chances of discovery of OGIBs. (Bresci G et al, 2005) Figure XX presents the suggested diagnostic algorithm for OGIBs, which recommends early use of CE after negative upper and lower endoscopy findings. The large majority of studies discuss the changes in patient management after capsule investigation, however failing to provide accurate information on the clinical outcome.…”
Section: Diagnostic Yield Comparison With Other Investigations and mentioning
confidence: 99%